2010
DOI: 10.1890/100103
|View full text |Cite
|
Sign up to set email alerts
|

Altering turbine speed reduces bat mortality at wind‐energy facilities

Abstract: Wind‐turbine operations are associated with bat mortality worldwide; minimizing these fatalities is critically important to both bat conservation and public acceptance of wind‐energy development. We tested the effectiveness of raising wind‐turbine cut‐in speed – defined as the lowest wind speed at which turbines generate power to the utility system, thereby reducing turbine operation during periods of low wind speeds – to decrease bat mortality at the Casselman Wind Project in Somerset County, Pennsylvania, ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
185
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(199 citation statements)
references
References 15 publications
8
185
1
1
Order By: Relevance
“…Although our scope of inference is limited to certain tree bats (L. borealis, L. cinereus, and L. noctivagans), areas of turbines from the rotorswept zone around the nacelle to near the ground (different behaviors may occur higher in the airspace), and are based on observations from just three turbines in midwestern North America, efforts to monitor bat activity near turbines (e.g., acoustic detectors and video cameras), or deter bats from turbines [e.g., devices producing startling sounds (51)] may benefit by aiming instruments from the back of the nacelle into the leeward airspace, an area where we consistently observed higher bat activity regardless of changing wind directions. Strategies for minimizing fatalities of bats at turbines currently focus on preventing blades from spinning during low wind periods (4,11,12). Our observations that tree bats show a tendency to closely investigate inert turbines and sometimes linger for minutes to perhaps hours (in the cases of clustered observations) highlight the plausibility of a scenario in which bats are drawn toward turbines in low winds, but sometimes remain long enough to be put at risk when wind picks up and blades reach higher speeds.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although our scope of inference is limited to certain tree bats (L. borealis, L. cinereus, and L. noctivagans), areas of turbines from the rotorswept zone around the nacelle to near the ground (different behaviors may occur higher in the airspace), and are based on observations from just three turbines in midwestern North America, efforts to monitor bat activity near turbines (e.g., acoustic detectors and video cameras), or deter bats from turbines [e.g., devices producing startling sounds (51)] may benefit by aiming instruments from the back of the nacelle into the leeward airspace, an area where we consistently observed higher bat activity regardless of changing wind directions. Strategies for minimizing fatalities of bats at turbines currently focus on preventing blades from spinning during low wind periods (4,11,12). Our observations that tree bats show a tendency to closely investigate inert turbines and sometimes linger for minutes to perhaps hours (in the cases of clustered observations) highlight the plausibility of a scenario in which bats are drawn toward turbines in low winds, but sometimes remain long enough to be put at risk when wind picks up and blades reach higher speeds.…”
Section: Discussionmentioning
confidence: 86%
“…Although causes of susceptibility remain unknown, altering turbine operations under certain conditions during periods of high risk can reduce bat deaths. Fatalities during late summer and autumn tend to occur when average wind speeds are lower than about 5-6 m/s (4, 9, 10), and studies in Canada (11), the United States (12), and Germany (4) demonstrated that bat deaths can be substantially reduced by preventing turbine blades from turning until winds reach such speeds. Such operational modifications at wind facilities bring logistical and financial costs but may prove to be effective at reducing bat fatalities in many areas (11,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the impacts of these fatalities may have broad-reaching ecological consequences. Although some wind energy facilities have successfully reduced the number of bat fatalities , Arnett et al 2011, fatalities of bats remain a conservation issue, especially given the important ecosystem services provided by bats. The combined losses of bats from whitenose syndrome (Frick et al 2010) and wind energy development could cost the North American agricultural sector billions of dollars/year (Boyles et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, most fatalities occur during low wind nights (<6 m/s) in late summer and the fi rst half of autumn, thus increasing the cut-in speed of the turbines on nights with high risk of bat collision would be an effective management tool to reduce mortality. Indeed, these methods have achieved reductions of bat fatalities from 50 to 90 % with marginal power loss (≤ 1 % of total annual output) (Baerwald et al 2009 ;Arnett et al 2011 ). Conversely, other management measures such as acoustic deterrents are less effective, in part due to rapid atmospheric attenuation of ultrasounds (Arnett et al 2013 ).…”
Section: Effects Of Solar Plants and Wind Farms On Wildlifementioning
confidence: 99%